2017
DOI: 10.15294/biosaintifika.v9i1.6783
|View full text |Cite
|
Sign up to set email alerts
|

Efect of Gamma 60Co Irradiation on The Growth, Lipid Content and Fatty Acid Composition of Botryococcus sp. Microalgae

Abstract: Botryococcus sp. is microalgae species that has high lipid content. Mutagenesis induced by Gamma 60

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…These fatty acids are omega 3 fatty acids, and there is linoleic acid which is 19.34% omega 6. When compared to the previous study (Ermavitalini et al, (2017), the linoleic and linolenic acids produced by B160 were 1.2 and 7-times higher respectively. At a high dose, B320 has several types of hydrocarbons.…”
Section: Resultscontrasting
confidence: 71%
See 3 more Smart Citations
“…These fatty acids are omega 3 fatty acids, and there is linoleic acid which is 19.34% omega 6. When compared to the previous study (Ermavitalini et al, (2017), the linoleic and linolenic acids produced by B160 were 1.2 and 7-times higher respectively. At a high dose, B320 has several types of hydrocarbons.…”
Section: Resultscontrasting
confidence: 71%
“…Mutagenic engineering using gamma irradiation to Botryococcus sp. has been increased biomass and lipid production up to 1.5 times (Ermavitalini et al, 2017). A similar study showed that Arthrospira platensis that irradiated with high-dose electron beam may increase lipid accumulation by about 30 -34 times higher than the control (Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…The exposure of gamma ray produces positive impact at low doses but generates negative impact on high doses that cause inhibition as well as decreasing level of growth and maturity of plant. Besides the irradiation applied on the plant, the effect produced by the exposure of gamma ray irradiation on microalgae also occurs as performed by Ermavitalini et al (2017) in which gamma ray with 10 Gy dose reveals deceleration phase in microalgae growth. The gamma ray radiation caused the cells on microalgae to experience oxidative stress which then triggered the cell to perform defensive process to maintain the growth and reduce the generated stress effect.…”
Section: Resultsmentioning
confidence: 99%